COMPETING PHENOMENON MODELLING OF TWO PHASE MULTI-FEED ZONE WELL IN ULUMBU GEOTHERMAL FIELD - Permatasari RB, Dinda
Optimization of production wells is one of the keys to the successful operation of a geothermal power plant. The ULB-1 was initially a production well, but its production was irregular or cyclic because it has a multi-feed zone. When the wellhead pressure is low, the produced fluid is a single phase, while at high wellhead pressure, a two-phase is produced. This study aims to analyze the feed zone’s area and characteristics and to model the wellbore and the reservoir to produce the maximum wellhead pressure that produces one vapor phase from the ULB-1 well. PTS analysis obtained three feed zones at 920 m, 790 m, and 690 m. Wellbore & reservoir models show a competing phenomenon around the feed zone area when the ULB-1 well is produced at a different WHP. The results of the wellbore modeling (top-down) obtained the maximum wellhead pressure to produce a single phase of steam, which is 4.8 bar with a mass flow rate of 5.73 kg/s of steam. Studying the coupled model between the wellbore and reservoir is recommended to get more representative results.